The Long-Term Predictive Properties of the Paris Classification in Paediatric Inflammatory Bowel Disease Patients. (27th September 2017) - Assa, Amit; Rinawi, Firas; Shamir, Raanan
Abstract: Introduction: The Paris modification of the Montreal classification for children with inflammatory bowel disease was accepted in 2011. We aimed to investigate the long-term clinical outcomes of patients diagnosed with IBD during childhood in a population-based cohort according to the Paris classification at diagnosis. Methods: The medical records of paediatric inflammatory bowel disease patients, diagnosed from 2000 to 2016, were reviewed retrospectively. Main outcome measures included time to first flare, hospitalisation, surgery, and biologic therapy. Results: In Crohn's disease patients [ n = 301, median age 14.2 years], colonic location was associated with higher prevalence of extraintestinal manifestations, whereas ileal location and complicated behaviour were associated with anti- Saccharomyces cerevisiae antibody positivity. During a median follow-up of 9.1 years (interquartile range [IQR]of 4.7–12.3), complicated behaviour at diagnosis was associated with increased risk for surgery (hazard ratio[ HR] = 2.7, p < 0.001] and hospitalisation [HR = 1.5, p = 0.01] but not with the risk for flare or stepping-up to biologic therapy. Isolated colonic disease was associated with a decreased risk of surgery [HR = 0.25, p = 0.02]. During a median follow-up of 8.5 years [interquartile range of 5.1–12], in patients with ulcerative colitis [ n = 126, median age 13.7 years], severe disease at diagnosis but not disease extent was associated with the risk for colectomy [HR = 3.5, p = 0.002], hospitalisation [HR = 3.3, p < 0.001], flare [HR = 2.4, p < 0.001] and biologic therapy [HR = 2.6, p = 0.001]. Conclusions: The Paris classification for paediatric inflammatory bowel disease has clear predictive properties. Complicated disease and ileal location at diagnosis in Crohn's disease, and severity of disease but not its extension in ulcerative colitis, predict long-term worse outcomes.